2017
DOI: 10.1186/s12940-017-0210-z
|View full text |Cite
|
Sign up to set email alerts
|

Early-life exposure to air pollution and greater use of academic support services in childhood: a population-based cohort study of urban children

Abstract: BackgroundThere is a growing literature showing associations between prenatal and early-life exposure to air pollution and children’s neurodevelopment. However, it is unclear if decrements in neurodevelopment observed in epidemiologic research translate into observable functional outcomes in the broader pediatric population. The objective of this study was to examine the association between early-life exposures to common urban air toxics and the use of academic support services, such as early intervention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Study of twins indicated genetic and environment affects various parts of brain. According to the study published in Journal of Nuclear Medicine in March shows that effect of genes on glucose metabolism plays a vital role in parietal lobe and left temporal lobe while environment effects can be seen in other regions of brain [15]. Hatazawa states about the mentioned study, although previous studies have examined considerable effect of genetic on volume of gray matter in the frontal cortex, this study shows that glucose metabolism in forehead is more affected by environmental factors.…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…Study of twins indicated genetic and environment affects various parts of brain. According to the study published in Journal of Nuclear Medicine in March shows that effect of genes on glucose metabolism plays a vital role in parietal lobe and left temporal lobe while environment effects can be seen in other regions of brain [15]. Hatazawa states about the mentioned study, although previous studies have examined considerable effect of genetic on volume of gray matter in the frontal cortex, this study shows that glucose metabolism in forehead is more affected by environmental factors.…”
Section: Resultsmentioning
confidence: 42%
“…Hatazawa states about the mentioned study, although previous studies have examined considerable effect of genetic on volume of gray matter in the frontal cortex, this study shows that glucose metabolism in forehead is more affected by environmental factors. If we know those parts of brain that are more affected by environment and pollutant agents, we will understand neurologic disorders and cognitive function better [15]. Reviewing selected papers in this research, it was found that…”
Section: Resultsmentioning
confidence: 99%
“…Individual and collective exposure measures were evaluated, but only isophorone displayed a crude association with BSF-R mental z-scores and was subsequently used for further assessments. To account for the rightly-skewed distribution, isophorone along with the other nine pollutants were dichotomized at the 75th quartile to obtain ‘high’ and ‘low’ exposure categories [ 32 , 36 ]. This approach reduces exposure measure susceptibility to overly influential outliers occurring when totaling the individual-level estimated exposure concentrations [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence highlights prenatal exposures to HAPs contributing to the disruption of fetal brain development introducing vulnerabilities to adverse neurodevelopment in children [ 31 , 34 , 35 ]. Previous studies showed the relationship between early life exposure to benzene, toluene, ethylbenzene, and xylene (BTEX), and neurodevelopment, as measured by the development of attention deficit/hyperactivity disorder (ADHD) as well as greater use of academic support services in children highly exposed to this form of air pollution [ 36 ]. Similarly, other studies have shown that early life exposure to diesel and PAH/POM, additional markers of pollution due to vehicular traffic, were associated with lower cognitive development scores in children [ 29 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The BTEX species are all HAPs. For example, numerous cohort studies and other epidemiology studies found correlation of benzene exposure to adverse health effects [10,11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%